Evaluation of mother and child protection card entries in a rural area of West Bengal - Bag, Subhadip; Datta, Mousumi (International Journal Of Community Medicine And Public Health, 2017)
Background: Mother and child protection card (MCPC) is a common card to maintain the record of health care delivery including ante natal care, post-natal care and care of the child that can be used by both the health personnel and the beneficiaries. Methods: Total 72 mothers of 0-2 years’ children residing at Banspool village were contacted and their MCPC were checked. From each of the five parts of the MCPC i.e. background and family information, information regarding pregnancy and childbirth, institution related information, antenatal care and post-natal care; maximum, minimum and median no of information boxes that were filled up were noted. Results: Information on background information and ante natal care recording was high with almost all the boxes were filled up but there was lack on maintenance of other records like post-natal care, immunization and growth chart. It was also found that beneficiaries are not making circle in the IFA tablets consumption part. Conclusions: The study reported gap in maintenance of proper health care delivery records through MCPC and more training for both the health personnel and mothers are needed for adequate use of the MCPC.